The influence of digital and vocational information literacy on student learning outcomes - Heru Setiyawan; Suharno Suharno; Nugroho Agung Pambudi (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2023)
Vocational students are confronted by intricate demands once they graduate. Despite the considerable need for vocational graduates in the workforce, most students have a limited understanding of digital and vocational information. This study used a descriptive quantitative method to determine the influence of digital and vocational information literacy on students' learning outcomes in three vocational schools in the Sragen Regency. Cluster Random Sampling was used to select a sample of 111 students. Data on digital and vocational information literacy were collected using a questionnaire, while those on the learning outcomes were obtained from the student's grades. The results showed that digital literacy influences vocational students' learning outcomes with a significance of 0.000 < 0.05. Vocational information literacy influences the students' learning outcomes with a significance of 0.000 < 0.05. Furthermore, digital and vocational information literacy simultaneously influence the students' learning outcomes with a significance of 0.000 < 0.05. These results indicate the necessity to familiarize and increase the students' literacy skills to improve learning outcomes. The results indicated that digital and vocational literacy partially and collectively influenced learning outcomes by 48.2%. Therefore, classroom instruction needs to be structured around learning models that actively stimulate the development of digital and vocational literacy skills, preparing students for workplace competitions. Consequently, teachers should consistently implement learning strategies that create a meaningful connection between the school environment and the realities of the professional world.